DOCUMENTING CONTRACTS IN SHARI’AH: RULES AND IMPLICATIONS IN AN ERA OF ADVANCES IN TECHNOLOGY - Dikko, Maryam (LexScriptio A Journal of the Department of Jurisprudence and Public Law, 2025)
This paper examines the rules governing the documentation of contracts under Islamic law, situating its analysis within both classical jurisprudence and contemporary applications. The mandate to record contracts, particularly financial transactions, is founded on Islamic legal injunction in Qur'an verse 2:282 which instructs believers to write down deferred transactions. The paper explores how classical jurists interpreted this directive and extended its application to various forms of contracts, emphasizing its role in safeguarding the rights and obligations of contracting parties. By analyzing the works of renowned jurists, such as Ibn Taymiyyah, and sources like Lisan al-Arab and Tafsir al-Qurtubi, the study highlights the evolution of contract documentation from mere moral exhortation to a legally recognized mechanism for dispute resolution and evidence in Islamic law. The dual methods of documentation, witnessing (al-Ishhaad) and writing (al-Kitabah)are explored alongside their legal and evidentiary implications. Furthermore, the paper addresses the relevance of contract documentation in modern contexts, particularly with the advent of digital contracts, blockchain technology, and smart contracts. It examines how contemporary Islamic legal thought reconciles traditional doctrines with emerging technological realities, ensuring that the maqasid al-shari‘ah (the higher objectives of Islamic law)are preserved in contractual dealings. The study concludes that the documentation of contracts in Islamic law transcends ritual obligation; it is a fundamental tool for ensuring justice, transparency, and the protection of rights. It also underscores the adaptability of Islamic legal principles in addressing contemporary contractual complexities, affirming the enduring relevance of Islamic jurisprudence in modern legal discourse please add one or two recommendations as well